Analisa Karakteristik Solar Dengan Kondensat Campuran Plastik Pasir Pembentuk Paving Block Melalui Uji Proximate dan Ultimate - Sidhi Adnyana, I Wayan; Suardana, Ngakan Putu Gede; Bandem Adnyana, I Wayan (Teknik Desain Mekanika, 2021)
Abstract There's an unresolved issue in Bali namely garbage. Trash that is often found is a type of plastic bag. Plastics have advantages over other materials, such as solid, lightweight, versatile, resistant to corrosion, not easily damaged, easy to paint, easy to mold, and good heat and electrical insulators. Plastics are made from petroleum, making it possible to produce alternative fuels when heated. Besides that, plastic can also be used as a material for making paving blocks. This research aims to determine the condensate content of the LDPE type plastic paving block with river sand (1:5 and 1:7 mass) as reinforcement at 200oC for 30 minutes of heating, and its effect on diesel fuel through proxymate test and ultimate test. In the proxymate test the moisture, fixed carbon, and ash content of 1: 5 condensate was higher than 1: 7 condensate, while the volatile content was lower. Condensate causes increase in the amount of moisture, fixed carbon, and ash but causes decrease in the amount of volatile diesel. In the ultimate test, carbon, nitrogen, oxygen, and sulfur content of 1: 5 condensate was lower than 1: 7 condensate but the amount of hydrogen was higher. The 1: 5 and 1: 7 condensates cause varying changes in the hydrogen, nitrogen and oxygen content of diesel fuel. Keyword : plastic, Fuel, proxymate, ultimate